Validasi Alat Ukur Taraf Muka Air Digital Sederhana Untuk Saluran Irigasi - Robby Yussac Tallar; Jimmy Agustian Loekito; Jonathan Chandra; Pin Panji Yapinus; Hendrik Lesmana; Leon Karsten; Tonny . (Jurnal Teknik Sipil, 2021)
Irrigation is an effort made by humans to irrigate agricultural land. Overall the irrigation system in Indonesia is an irrigation building that starts from a water taking area or a weir and distributes it to various agricultural areas through primary dividing channels to the quarter. This requires supporting infrastructure in the process of extracting / distributing water from water sources to irrigation plots. One of the main irrigation infrastructures is irrigation channels with a means of regulating or measuring the discharge at the upstream such as a water gauge board or manual peilchaal to measure the water level that passes through an irrigation channel. The main objective of this research is to plan a digital water level measuring instrument in the irrigation channel to make it easier for sluice guard officers or farmers to find out the flow rate that passes through an irrigation channel. The data that will be collected are primary data generated from the experimental results by comparing the results from manual and digital. These data are in the form of water level data on the Thomson measuring instrument to find the flow rate through the open channel model. Based on the research results, it can be concluded that the validation results obtained from digitization have a very high level of accuracy. The percentage value difference between the value obtained from the manual and digital level meter has an average value of 1-6%. The amount of this percentage is strongly influenced by the decimal digits that have not been compared to those read on the manual level meter. Therefore, in the future, its capacity to read the water level accurately to the nearest digit will be increased.